2023
DOI: 10.3389/fmolb.2023.1134253
|View full text |Cite
|
Sign up to set email alerts
|

LTF induces senescence and degeneration in the meniscus via the NF-κB signaling pathway: A study based on integrated bioinformatics analysis and experimental validation

Abstract: Background: The functional integrity of the meniscus continually decreases with age, leading to meniscal degeneration and gradually developing into osteoarthritis (OA). In this study, we identified diagnostic markers and potential mechanisms of action in aging-related meniscal degeneration through bioinformatics and experimental verification.Methods: Based on the GSE98918 dataset, common differentially expressed genes (co-DEGs) were screened using differential expression analysis and the WGCNA algorithm, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…By activation of the NF-B signaling pathway, LTF might cause meniscal senescence and degeneration. These findings suggested that LTF may serve as a possible treatment target for meniscal degeneration associated with aging as well as a diagnostic marker . In primary chondrocytes, DPP-4 expression was linked to increased senescence-related β-galactosidase activity, p16 expression, senescence-related gene and catabolic gene expression (ADAMTS5, MMP13, IL6, and IL8), increased senescence-associated secretory phenotype secretion, and decreased anabolic gene expression (COL2A1 and ACAN) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…By activation of the NF-B signaling pathway, LTF might cause meniscal senescence and degeneration. These findings suggested that LTF may serve as a possible treatment target for meniscal degeneration associated with aging as well as a diagnostic marker . In primary chondrocytes, DPP-4 expression was linked to increased senescence-related β-galactosidase activity, p16 expression, senescence-related gene and catabolic gene expression (ADAMTS5, MMP13, IL6, and IL8), increased senescence-associated secretory phenotype secretion, and decreased anabolic gene expression (COL2A1 and ACAN) .…”
Section: Discussionmentioning
confidence: 91%
“…These findings suggested that LTF may serve as a possible treatment target for meniscal degeneration associated with aging as well as a diagnostic marker. 41 In primary chondrocytes, DPP-4 expression was linked to increased senescence-related β-galactosidase activity, p16 expression, senescence-related gene and catabolic gene expression (ADAMTS5, MMP13, IL6, and IL8), increased senescence-associated secretory phenotype secretion, and decreased anabolic gene expression (COL2A1 and ACAN). 42 In this study, 25 hub cellular senescence-related DEGs were selected, their important biological roles were described, and correlation networks were built by using a variety of bioinformatic techniques.…”
Section: Discussionmentioning
confidence: 97%
“…For example, LTF binding to CD14 receptor competes with the bacterial LPS (product of dying bacteria) [ 44 ] and can attenuate NF-κB-induced transcription of genes for various inflammatory mediators [ 45 ]. Also, it is reported that high LTF expression might contribute to meniscal aging and degeneration through the NF-κB signaling pathway [ 46 ].Therefore, we could speculate that the endothelial-immunology transition is regulated by Ltf.…”
Section: Resultsmentioning
confidence: 99%
“…S8 D). It is well-known that LTF could activate the NF-κB signaling pathway, promoting macrophage activation [ 43 ].Also, it is reported that high LTF expression might contribute to meniscal aging and degeneration through the NF-κB signaling pathway [ 46 ].Therefore, we could speculate that the endothelial-immunology transition is regulated by Ltf.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB controls the SASP as many components are NF-κB target genes 39 and increased NF-κB phosphorylation has been detected in senescent cells of different origin. [39][40][41][42][43] An increase in secretory activity is driven by the high NAD+/NADH ratio produced by the high mobility group A proteins (HMGA)-nicotinamide phosphoribosyltransferase (NAMPT) axis, along with increased glycolysis and mitochondrial respiration. SASP factors in turn alter NAD+ metabolism and stimulate the expression on immune cells of CD38, a NADase which leads to NAD+ reduction.…”
Section: Stimulator Of Interferon Genes (Sting)mentioning
confidence: 99%